Effect of Good Corporate Governance on Profitability - Devina Subarnas; Yuliana Gunawan (Master of Accounting Universitas Trunojoyo Madura, 2019)
The research aims to decide the effect of good corporate governance on profitability in banking companies listed on Indonesia stock exchange from 2016 to 2017. This researchwas an explanatory research, using secondary data. The sample was selected using the purposive sampling method, which resulted in a total of 28 sample companies. The data analysis used was multiple linear regression. The results show that the board of directors significantly affect profitability and independent commissioners does not significantly affect profitability. Simultaneously, board of directors and independent commissioners significantly affect profitability.